Experimental Study on the Effect of Freeze–Thaw Cycles on the Apparent and Mechanical Properties of Rubber Concrete Under Chloride Environment - Huang, Xin; Wang, Tingya; Pang, Jianyong; Song, Fangnian (Arabian journal for science and engineering (2011), 2022)
Rubber concrete (RC) is a new type of concrete that has been rapidly gaining acceptance in recent years. In this paper, the effects of freeze–thaw cycles in chloride salt solution on the spalling amount ( Q s ), relative wave velocity ( V R ) and relative compressive strength ( σ R ) of ordinary concrete (OC) and RC were investigated using the test method of one-sided freezing with rubber particle size and content as the main investigating factors, and the effect of moisture content of RC on relative compressive strength at low temperature (− 20 °C) was investigated in combination with the air-entraining property of rubber. The comprehensive performance of rubber concrete under the influence of multiple factors ( Q s , V R , σ R ) was also evaluated with the efficacy factor method. Finally, the internal structural changes of rubber concrete after salt freezing were observed by Scanning Electron Microscope (SEM), and the reasons for the changes in physical and mechanical properties of RC were analyzed from a microscopic perspective. The results show that RC has less spalling, higher relative wave velocity and compressive strength than OC, indicating that rubber can improve the frost resistance of concrete. The content of RC has a significant effect on the freeze–thaw cycle, and the RC with 10% content has a smaller amount of spalling and a higher relative wave velocity and compressive strength. The effect of particle size on RC is not obvious. The spalling amount and relative wave velocity of 3–6 mm particle size is the best, while the relative compressive strength of 1–3 mm particle size is the best. In addition, the smaller the particle size of RC, the higher its moisture content, the greater the impact on its low-temperature compressive strength. The efficiency coefficient of the above indexes shows that the overall performance of concrete with 10% rubber content is better than that of other contents, under this content, the comprehensive performance of 3–6 mm RC is the best. The change of microstructure shows that the internal structure of OC is more porous than that of RC with the increase of freeze–thaw cycles, however, the larger the rubber particle size, the more needle crystals in the pore structure of concrete.